The Importance of Didactic Conditions in Improving the Independent Education of Students - Khaitova Shakhnoza Daniyarovna; Nurmukhamdieva Lola Alisherovna (Genius Journals, 2023)
Today, the concept of modern education is that the student should learn by himself. The teacher’s role is to manage his teaching, that is, to stimulate, organize, activate, coordinate and advise his activities. One of the main tasks of the concept of modernization of education of the Republic of Uzbekistan is the formation of a creative personality
Keywords: Independent education; activation; pedagogical process